Retracing the Text: Francisco Brines' Poemas excluidos - Judith Nantell (Studies in 20th & 21st Century Literature, 1989)
In 198S Francisco Brines published Poemas excluidos [Excluded Poems]. In this work he included, ironically and paradoxically (considering the title), various poems that had been excluded from his previously published collections of poetry. This essay investigates the critical activity of reconstructing the text within the included-excluded intertextual context of Brines' poetic production. In particular, as will be shown, Poemas excluidos demonstrates the play of texts and play of meaning that constitute the complex object the literary critic seeks to describe. One aspect of the play of texts evident in this work is that the poem is a symbiont not only of other poems of the collection but also of earlier and later poems of Brines' other collections. From this symbiosis arises the interplay of texts and the indeterminacy of meaning of Poemas excluidos. Textual reconstruction yields yet another important result. As critics attempt to untangle the tangle of texts, they become more and more caught up in the snarl of texts, and the play of meaning of the object scrutinized. Critical commentary, then, itself becomes yet one more thread in the intricate intertextual web of Poemas excluidos.
Keywords: 198S; Francisco Brines; Poemas excluidos; Excluded Poems; ironically; paradoxically; included-excluded; poetry; object; text; symbiont; collection; Critical commentary